Associations between serum S100A8/S100A9 and knee symptoms, joint structures and cartilage enzymes in patients with knee osteoarthritis. Issue 1 (January 2019) - Ruan, G.; Xu, J.; Wang, K.; Zheng, S.; Wu, J.; Ren, J.; Bian, F.; Chang, B.; Zhu, Z.; Han, W.; Ding, C.
Summary: Objective: Animal studies suggest that S100A8/S100A9 may be involved in the pathogenesis of osteoarthritis (OA); however, there has been no clinical study examining the associations between serum S100A8/S100A9 and knee symptoms, joint structures and cartilage degradation enzymes in knee OA patients so far. Therefore, this study was designed to investigate the cross-sectional associations between serum levels of S100A8/S100A9 and the outcomes in patients with knee OA. Design: A total of 141 subjects with clinical knee OA were included. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score was used to assess joint symptoms. Magnetic resonance imaging (MRI) was used to measure knee structural abnormalities including cartilage defects. Knee radiography was used to assess joint space narrowing (JSN), osteophytes and the radiographic severity of OA. Enzyme-linked immunosorbent assay (ELISA) was used to measure the serum levels of S100A8/S100A9, matrix metalloproteinase (MMP)-3, MMP10 and MMP13. Results: In multivariable analyses, serum S100A8/S100A9 were positively associated with total WOMAC score (β: 0.111 per 10 ng/ml, P = 0.021), WOMAC weight-bearing pain (β: 0.015 per 10 ng/ml, P = 0.043) and WOMAC physical dysfunction (β: 0.091 per 10 ng/ml, P = 0.010), and had positive associations with total cartilage defects and cartilage defects at lateral femoral, lateral tibial and medial femoral sites (ORs: 1.006–1.008 per 10 ng/ml, all P < 0.05) and serum levels of MMP3 (β: 0.002 per 10 ng/ml, P = 0.032) in patients with clinical knee OA. Conclusions: Serum levels of S100A8/S100A9 were positively associated with increased knee symptoms, cartilage defects and serum cartilage degradation enzymes in patients with knee OA, suggesting that S100A8/S100A9 may have a role to play in knee OA. Future longitudinal studies are required to confirm these findings.